Haplorchis taichui: Worm recovery rate and immune responses in infected rats (Rattus norvegicus) - Saenphet S. (2014)
Worm recovery rate, mucosal mast cells (MMCs), eosinophils and serum IgE concentration in rats were investigated after orally feeding 300 Haplorchis taichui metacercariae to male rats. The duodenal, jejunal and ileal tissue sections were stained with 1% alcian blue and 0.5% safranin-O for MMC count. Eosinophil count and the serum IgE concentration assay were measured from cardiac puncture blood. The average worm recovery rates were 20.00%, 13.00%, 0.67%, 1.67% and 0.00% on day 3, 7, 14, 21 and 28 post-infection (PI), respectively. The number of MMCs in the infected rats were significantly higher than in the controls (P < 0.01), reaching a peak on day 21 PI. They decreased thereafter, with the decline in worm recovery. Eosinophil count and Serum IgE concentration were also increased but not significantly higher than the controls. However, they showed a positive relationship to worm recovery. It could be concluded from the results that MMCs, eosinophils and IgE may play an important role in the expulsion of H. taichui from rat intestine. However, the mechanism by which the MMC result in the helminth expulsion still need to be understood, and it is recommended that other cells such as goblet cells be studied further. © 2008 Elsevier Inc. All rights reserved.